2020
DOI: 10.1007/s00270-020-02727-8
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Intravenous Thrombolysis Offers No Benefit in Mechanical Thrombectomy in Optimized Tertiary Stroke Center Setting

Abstract: Purpose Mechanical thrombectomy (MT) is the first-line treatment in acute stroke patients presenting with large vessel occlusion (LVO). The efficacy of intravenous thrombolysis (IVT) prior to MT is being contested. The objective of this study was to evaluate the efficacy of MT without IVT in patients with no contraindications to IVT presenting directly to a tertiary stroke center with acute anterior circulation LVO. Materials and Methods We collected the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We included 12 eligible studies (3 RCTs 19 , 20 , 21 and 9 observational studies 22 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ) for the final quantitative analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 12 eligible studies (3 RCTs 19 , 20 , 21 and 9 observational studies 22 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ) for the final quantitative analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies only included patients with acute ischemic stroke involving the anterior circulation, except 2 studies 22 , 29 that included patients involving both anterior and posterior circulation occlusion. Among 9 observational studies, 5 studies 22 , 30 , 31 , 33 , 34 , 35 provided propensity score matching analysis results. One study 29 included patients within a 3‐hour time window.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and effectiveness of administrating IV tPA prior to MT for patients with AIS is still a debatable matter. Although the current guideline recommends using the IV tPA prior to MT (BT) [ 31 ], some recent RCTs and observational studies found no significant difference in functional outcomes between patients receiving BT and dMT [ 35 , 42 , 44 , 45 , 53 , 55 , 56 , 58 , 59 ]. Furthermore, a lower rate of sICH in favor of dMT has been reported [ 42 , 53 , 55 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…We deemed nine of the 73 reviewed studies to be eligible. Three RCTs (DIRECT-MT, DEVT and SKIP [20][21][22] ) and six observational studies [23][24][25][26][27][28] were included after the full texts of the studies were screened. In all nine studies, patients with AIS-LVO who were eligible to undergo both IVT and EVT were assigned to undergo direct EVT or to undergo a combined treatment with intravenous alteplase before EVT.…”
Section: Study Characteristicsmentioning
confidence: 99%